PELATIHAN E-COMMERCE PRODUK WISATA BERBASIS SMARTPHONE - Negara, I.M.K.; Sagita, P.A.W.; Dewi, L.G.L.K.; Juwitasari, W.C.; Adnyana, I.G.S. (Buletin Udayana Mengabdi; Vol 23 No 1 (2024): Buletin Udayana Mengabdi, 2023)
The village government has sought to support tourism through the establishment of a tourist awareness group, namely Pokdarwis. Pokdarwis communicates the barriers in particular the information technology and communication in the distribution, sale, and purchase of its products, as well as in the marketing of the tourism products it has. The problems faced require solutions in the form of understanding activities as well as partner skills in using smartphones for e-commerce activities. Implementation methods include technology transfer methods as well as evaluation and monitoring. Activities were stimulated with high enthusiasm by tourist activities in the village of Bongan Tourism. They have a good understanding of how e-commerce benefits the marketing of tourist products such as teh gobo (teh gonda bongan). In addition to knowledge about the use of smartphones as a medium, that is also optimal in the marketing of the products they have. This dedicated activity affects the independence of partners in the use of e-commerce. Keywords: bongan village, e-commerce, smartphone